2014
DOI: 10.1108/jidob-08-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Life Skills Group: increasing foundation knowledge and motivation in offenders with a learning disability

Abstract: Purpose – Offenders with a learning disability present with greater clinical need than those without a learning disability. However, for this client group, access to and engagement with psychological and criminogenic interventions are often limited. The purpose of this paper is to discuss a potentially useful approach to this issue. Design/methodology/approach – A single case study design was used to evaluate an introductory group progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Evaluations of 5 non-specialist group interventions delivered to adults with intellectual disabilities and/or autism who set fires included a structured cognitive behavioural anger management training package developed by Williams and Barlow (1998), an adapted dialectical behaviour therapy program developed by Ingamells and Morrissey (2014), a cognitive behavioural life skills group treatment programme (Patterson & Thomas, 2014), and social skills training (Rice & Chaplin, 1979).…”
Section: Offence Related Characteristicsmentioning
confidence: 99%
“…Evaluations of 5 non-specialist group interventions delivered to adults with intellectual disabilities and/or autism who set fires included a structured cognitive behavioural anger management training package developed by Williams and Barlow (1998), an adapted dialectical behaviour therapy program developed by Ingamells and Morrissey (2014), a cognitive behavioural life skills group treatment programme (Patterson & Thomas, 2014), and social skills training (Rice & Chaplin, 1979).…”
Section: Offence Related Characteristicsmentioning
confidence: 99%
“…First, promising results were found for a three session group motivational interviewing intervention for offenders with LD and alcohol-related problems (Mendel and Hipkins, 2002). Moreover, Patterson and Thomas (2014) used a case study design to demonstrate that a life skills group incorporating a motivational component for offenders with LD resulted in increased readiness to change, and motivation to engage in the group. Though promising, this study did not examine if the increase in readiness to change resulted in an actual change in behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Practitioner attitudes to persons with cognitive impairment have been found to affect the level of engagement between practitioner and client. Practitioner perceptions that lead to a reluctance to work with persons with disability and MBIF have been found to be that working with this group is difficult and time-consuming when seeking to present and convey information in a way that can be understood by the client (Patterson and Thomas, 2014); that they are perceived to be difficult to include in group-work because of their reduced level of regulation or their lack of confidence in their ability in social situations, and because of their negative previous experiences in school group work; and low levels of motivation and ability to comply with treatment, therapy and other requirements (O'Mahony and Hearne, 2008, Edwards et al, 2007, Mason and Murphy, 2002, Hayes et al, 1995.…”
Section: Criminal Justice Agenciesmentioning
confidence: 99%
“…It is well documented in the literature that treatment and skills development programs in prison have not met the learning needs of those with cognitive impairments (Hayes, 2004). Studies in the UK also found that, in prisons, the presence of a cognitive impairment is often used as exclusion criteria for participation in treatment programs (Patterson andThomas, 2014, Goodman et al, 2011).…”
Section: Clinicians and Clinical Programsmentioning
confidence: 99%
See 1 more Smart Citation